PERANCANGAN ENVIRONMENTAL GRAPHIC DESIGN UNTUK SEA WORLD ANCOL: Environmental Graphic Design for Sea World Ancol - Chen, Carren Miquella; Hananto, Brian Alvin; Wijaya, Ade Maradhona Shantio (Jurnal Dimensi DKV: Seni Rupa dan Desain, 2024)
Environmental Graphic Design for Sea World Ancol. Sea World Ancol is the first oceanarium in Indonesia, located within Taman Impian Jaya Ancol, and is very popular among the public. Between 2022 and 2023, the number of visitors increased rapidly, making the Environmental Graphic Design (EGD) system essential for navigating and conveying information to visitors. This research aims to identify issues and provide better design solutions for the EGD at Sea World Ancol. The methodology follows the design phases proposed by Calori and Vanden-Eynden, starting with the pre-design phase to collect and analyze data through observation, document studies, questionnaires, interviews, and literature reviews. The design phase includes the development of schematic concepts, design development, and documentation. Thus, this design project aims to produce a new EGD for Sea World Ancol that is effective in terms of graphics, information, and hardware systems.